Development of neuromodulation and localization research on implantable device - Hong-wei HAO; Yuan YUAN; Lu-ming LI (Chinese Journal of Contemporary Neurology and Neurosurgery, 2015)
After over twenty years of clinical research and application, neuromodulation technology has significant efficacy and broad prospect in movement disorders, pain, epilepsy and psychiatric diseases. In this paper, localization process and future trends of typical neurostimulation systems such as deep brain stimulator and vagus nerve stimulator were introduced.   DOI: 10.3969/j.issn.1672-6731.2015.09.004